Brain abnormalities in COVID-19 acute/subacute phase: A rapid systematic review (2020)
Objective This systematic review aimed to synthesize early data on typology and topography of brain abnormalities in adults with COVID-19 in acute/subacute phase. Methods We performed systematic literature search via PubMed, Google Scholar and ScienceDirect on articles published between January 1 and July 05, 2020, using the following strategy and key words: ((covid[Title/Abstract]) OR (sars-cov-2[Title/Abstract]) OR (coronavirus[Title/Abstract])) AND (brain[Title/Abstract]). A total of 286 non-duplicate matches were screened for original contributions reporting brain imaging data related to SARS-Cov-2 presentation in adults. Results The selection criteria were met by 26 articles (including 21 case reports, and 5 cohort studies). The data analysis in a total of 361 patients revealed that brain abnormalities were noted in 124/361 (34%) reviewed cases. Neurologic symptoms were the primary reason for referral for neuroimaging across the studies. Modalities included CT (-angiogram, -perfusion, -venogram), EEG, MRI (-angiogram, functional), and PET. The most frequently reported brain abnormalities were brain white matter (WM) hyperintensities on MRI 66/124 (53% affected cases) and hypodensities on CT (additional 23% affected cases), followed by microhemorrhages, hemorrhages and infarcts, while other types were found in <5% affected cases. WM abnormalities were most frequently noted in bilateral anterior and posterior cerebral WM (50% affected cases). Conclusion About a third of acute/subacute COVID-19 patients referred for neuroimaging show brain abnormalities suggestive of COVID-19-related etiology. The predominant neuroimaging features were diffuse cerebral WM hypodensities / hyperintensities attributable to leukoencephalopathy, leukoaraiosis or rarefield WM.